Surgical treatment of lingual frenectomy: Case report (Research, Society and Development, 2021)
Ankyloglossia, also popularly known as "tongue stuck" is a congenital anomaly, defined as a median crease located on the back of the tongue and close to the buccal floor, which extends to the lingual face of the alveolar crest. It consists of folds of the mucous membrane, connective tissue rich in collagen and elastic fibers, fatty tissue and muscle fibers, in addition to blood vessels protected by stratified squamous epithelial tissue. It has the function of assisting in the three-dimensional movement of the tongue, swallowing, diction and suction. In cases of congenital alterations, there are limitations to the lingual movements, periodontal, orthodontic, prosthetic interferences, in addition to socialization. The surgical indication is usually diagnosed by dentists, speech therapists and pediatricians, and can be treated surgically at any age using conventional techniques and other techniques described in the literature, with the aid of cold blades, electrocautery or surgical laser. The objective of this work is to report the case of lingual frenectomy in a 15-year-old male patient.